SURVEY FOR DIFFERENT KINDS OF AQUATIC MICROPHYTES FOUND AT MUZAFFARPUR - GUDDI KUMARA (International Journal of Multidisciplinary Research and Studies, 2020)
The current study was carried out in Manikamaun wetland located in North Bihar, where Macrophyte diversity and biomass estimation was observed from June 2019 to March 2020. A total of 24 species of macrophytes belonging to 15 families were recorded from the wetland. From the identified species, Hydrocharitaceae (3), Potamogetonacea (3), Poaecae and Cyperaceae (2 each) were found dominant. Biomass productivity of observed macrophytic plants was estimated, Aquatic macrophytes were categorized in 4 types, viza, Free-floating plants (40%), Submerged (33%), Rooted with floating leaves (25%) and emergent (2%). Maximum biomass was recorded in month of February 387.91 g/m2 and minimum during the month of July 123.27 g/m2, a total of 2541.88 g/m2 of biomass was recorded from the maun. Among the various macrophyte species reported, highest biomass contributor was Eichhornia crassipes 1293.26 g/m2, followed by Najas graminea (610.17 g/m2 ), Nelembo nucifera (562.75 g/m2 ), and Hydrilla verticellata (221.24 g/m2 ). The aquatic ecosystem is composed of aquatic flora and fauna which interact together in maintaining the aquatic ecosystem. Aquatic macrophytes are macroscopic forms of aquatic vegetation, including macro algae, mosses, ferns and angiosperms found in aquatic habitat. Macrophytes of freshwater ecosystems have diverse roles to play in the structure and functioning of these aquatic ecosystems.